Studies of Some Transition Metal Chelate Monomers - Sharma, Sangita; J. Vvora, Jabali; Joshi, J.D (Asian Journal of Chemistry, 2010)
Some metal chelates of monomers have been synthesized by the interaction of Ni(II), Cu(II), Cr(III) and Fe(III) acrylate with 2,2'-bipyridylamine in alcohol. All these metal chelate monomers are coloured, crystalline powders insoluble in many of the organic solvents. They are characterized by UV-visible spectra, infrared spectra, elemental analysis, thermogravimetric analysis and megnetic susceptibility measurements. All metal chelate monomers show a six coordinated structure and suggest octahedral geometry. Conductometric studies indicate that these metal chelate monomers are non-electrolytes.